MAPPING GEOGRAPHICAL OF CHILDREN'S NUTRITIONAL DISORDERS IN BUKITTINGGI - Lubis, Kholilah; Ramadhanti, Indah Putri; Kustanto, Debby Ratno (LPPM Universitas Prima Nusantara Bukittinggi, 2022)
Background: Children’s Nutritional Disorders (CND) are diseases that occur when childhood’s dietary intake doesn't contain the proper amount of nutrients for healthy functioning. In Indonesia, the prevalence of severely underweight is 1,4%, underweight is 6,7%, 1,1% were severely wasted and 4,3% of children were wasted. The prevalence of stunted has decreased from 27,7% in 2019 to 24,4% in 2020. However, this achievement is still far from the SDG’s targets.Objective: This study aims to determine the CND with a mapping geographical that can help the government to find the cause so the cases decrease faster.Methods: This study was descriptive with a cross-sectional design and conducted in Bukittinggi, West Sumatera, and used secondary data (Height and Weight Measurement Reports in 2020) from Public Health Office. To present the mapping geographical using QGIS 3.16 by taking the coordinate points of the Community Health Center in the Bukittinggi area.Results: Severely underweight, Guguk Panjang (7,55%) vs. Nilam Sari (0%). Underweight, Tigo Baleh (12,33%) vs Nilam Sari (1,55%). The risk of overweight, Tigo Baleh 23,33% vs. Gulai Bancah (4%). Severely stunted, Tigo Baleh (5,19%) vs. Gulai Bancah (3,60%), Nilam Sari (1,06%). Stunted, Guguk Panjang (15, 81%) vs. Gulai Bancah (14,75%). Severely wasted is very low in each Community health center (0,02% or 0,01%). Wasted, Tigo Baleh (0,91%) vs. Mandangin (0,08%). Overweight, Guguk Panjang (9,62%) vs. Gulai Bancah (6,12%).Conclusion: The risk of overweight is the most cases of CND in Bukittinggi, while severely wasted is the lowest case. The cases in 2020 increased associated with the Covid-19 pandemic.